Aspectuality and temporality : descriptive and theoretical issues - Guentchéva, Zlatka (Studies in language companion series, 2016)
This volume brings together a collection of articles exploring tense and aspect phenomena in a variety of non-related languages: Indo-European (Albanian, Bulgarian, Armenian, English, Norwegian, Hindi), Hamito-Semitic (Berber, Zenaga Berber, Arabic varieties, Neo-Aramaic), African (Wolof, Langi), Asian (Badaga, Korean, Mongolian languages - Khalkha, Buriat, Kalmuck - Thaï, Tibetic languages), Amerindian (Yucatec Maya, Sikuani), Greenlandic (Eskimo) and Oceanian (Nêlêmwa). Each article is grounded in solid empirical knowledge. It offers an in-depth study of aspectual and temporal devices as man.